FEATURES OF SPEECH FORMS OF ADDRESS IN ENGLISH DISCOURSE IN COMPARISON - Shaxnoza Artikova (Journals Park Publishing, 2022)
Language is a complex social phenomenon; it exists in the human society, in the real everyday practice of people belonging to different social, professional and territorial strata of society, and is therefore characterized by certain variability in the scope of this community.
Keywords: pneumatic-mechanical; basis of speech sounds; words and sentences